Assessment of Biocompatibility and Physical Properties of Ni-Ti-Zr-Nb Shape Memory Alloys - Abdullah, S. S.; Balci, E.; Qader, I. N.; Dagdelen, F. (Springer India, 2023)
Ti-Ni-based shape memory alloys (SMAs) are among the alloys used as biomaterials. The degree of biocompatibility can be improved by adding different biocompatible elements to these alloy families. In this study, the microstructure, phase transformation temperatures, and biocompatibility of Ti-Ni-Nb-Zr SMAs were investigated by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), optical microscopy (OM), differential scanning calorimetry (DSC), and electrochemical potentiodynamic measurements, respectively. The arc melting method was used to manufacture alloys with nominal compositions of Ti-10Zr-(40-x) Ni-xNb ( x = 0 , 2 and 4 at.%). The phase transformation of B19 '<-> B2 was observed in DSC results, which indicated that the alloys have shape memory behavior. Although martensite plates and dendritic structures are noticeable in OM images, XRD and SEM analyses revealed beta-Nb, B19 ', B2, and some precipitation phases. The corrosion resistance of the alloys was determined by potentiodynamic corrosion analysis. The alloy with 2 at. % Nb instead of Ni showed the best degree of biocompatibility compared to the other alloys.
Keywords: Shape memory alloys; Ti-Ni-Zr-Nb; Microstructure; Biocompatibility; Corrosion resistance